Greenhouse gas balance due to the conversion of sugarcane areas from burned to green harvest in Brazil - De Figueiredo, Eduardo Barretto [UNESP]; La Scala, Newton [UNESP] (Elsevier B.V., 2011)
Strategies for the reduction of greenhouse gas emission in agriculture have been debated for some time, especially in Brazil, where the agricultural sector is an important contributor to the national emission balance. The present study focuses on the change in greenhouse gas balance from the conversion of sugarcane areas from burned to green harvest, considering both agricultural and mobile sources. The results are presented in terms of CO(2) equivalent, using the gases CO(2), CH(4) and N(2)O, and indicate that N synthetic fertilizer and burning of residues are responsible for the higher emissions observed in green and burned areas, with 1167.6 and 941.0 kg CO(2)equiv.ha(-1) y(-1), respectively. The sugarcane burning plot presented the highest emissions in our scope, with 3103.9 kg CO(2)equiv.ha(-1) y(-1). Our estimates indicate that conversion from burned to green plot could save from 310.7 (not considering soil carbon sequestration) to 1484.0 kg CO(2)equiv.ha(-1) y(-1) (considering soil carbon sequestration). The development of ethanol and sugar production in Brazil should certainly move towards the reduction of burning practice and diesel use, avoiding some tillage operations and should also adopt more efficient fertilization practices to reduce N fertilizer inputs, attaining reduction in greenhouse gas emissions from the sugarcane agricultural sector. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: greenhouse gas; Sugarcane; Harvest system; Carbon balance; CO(2) emission